ANALYSIS OF PLATELET-LYMPHOCYTE RATIO IN TYPE 2 DIABETES MELLITUS AS A SYSTEMIC INFLAMMATION BIOMARKER - Fathul Hidayatul Hasanah; Sri Wahyuni; Danny Meganingdyah Primartati; Aulia Risqi Fatmariza; Fita Sari (Meditory : The Journal of Medical Laboratory, 2026)
Background: Chronic hyperglycemia in type 2 DM causes chronic low-grade systemic inflammation, which triggers complications. The body responds with an increase in proinflammatory cytokines and changes in blood cell hemostasis. The platelet lymphocyte ratio (PLR) is a new inflammatory marker that has clinical prognostic value. Objective: Comparison of PLR values in type 2 DM without complications with the cardiovascular and nephropathy complication groups. Methods: The study employed a retrospective research design and included a total of 617 respondents with type 2 DM. The respondents were divided into three groups: 162 with uncomplicated type 2 DM, 291 with cardiovascular complications, and 164 with nephropathy. The data was collected from Mojowarno Christian General Hospital in Jombang. Results: The mean value of PLR in uncomplicated type 2 DM was 238.4 ± 225, in cardiovascular 327.11 ± 162, and in nephropathy 449.52 ± 107. The difference test yielded a statistically significant result p < 0.001, indicating that there were notable differences in PLR values across the three type 2 DM groups. Conclusions: There is a difference in PLR values in type 2 DM between the group without complications and the group with complications (cardiovascular and nephropathy).